Best Practices in Customs Reform - Lessons from Morocco - De Wulf, Luc (World Bank, Washington, DC, 2012)
Successful trade policy reform, often requires customs reform. In the 1990s Morocco's trade policies were strongly influenced by its agreement with the European Union, with the World Trade Center, and the Multi-fiber Agreement, which led the Customs and Indirect Taxes Administration to examine its procedures. Customs reforms were based on the principles of the World Customs Organization, supported by technical assistance provided by the International Monetary Fund and bilateral partners. Such reforms were the result of public-private partnerships, focused on four main areas: 1) simplified procedures and selective controls; 2) increased use of information technology; 3) improved management of special customs procedures; and, 4) enhanced transparency and partnerships with the private sector.